Human Cytomegalovirus Immediate Early Protein 2 Protein Causes Cognitive Disorder by Damaging Synaptic Plasticity in Human Cytomegalovirus-UL122-Tg Mice - Wang, Zhifei; Yu, Wenwen; Liu, Lili; Niu, Junyun; Zhang, Xianjuan; Nan, Fulong; Xu, Lili; Jiang, Bin; Ke, Dingxin; Zhu, Wenhua; Tian, Zibin; Wang, Yashuo; et al. (Frontiers in Aging Neuroscience, 2021)
Human cytomegalovirus (HCMV) infects most human populations around the world and could cause neurologic disabilities. Previous studies have shown that immediate early protein 2 (IE2, also named as UL122) of HCMV are related with the cognitive disorder mechanism. Due to the species isolation, a HCMV-infected animal could not be established that lead the study about long-term effects of IE2 on neural development could not be carried out. By establishing the C57BL/6-Tg (HCMV-UL122) mice (UL122 mice), we explored the cognitive behavior and complexity of neurons changes in this transgenic UL122 mice which consistently express IE2 protein in different age (6- and 12-month). In the morris water maze, cognitive impairment was more pronounced in 12-month UL122 mice than in 6-month ones. At the same time, a decrease of the density of dendritic spines and branches of dendritic in the hippocampal neurons of 12-month was observed. Moreover, long-term potentiation was showed to be impaired in 12-month UL122 mice. Several synaptic plasticity regulated molecules were translationally reduced in 12-month UL122 mice, including scaffold proteins postsynaptic density protein 95 (PSD95) and microtubule-associated protein 2 (MAP2). The expression of IE2 was increased in 12-month mice compared with 6-month and statistical analysis suggested the cognitive damage was not caused by animal natural aging, which may be used to exclude the effect of natural aging on cognitive impairment. All these results draw a conclusion that IE2 play as a pathogenic regulator in damaging the synaptic plasticity by down regulating the expression of plasticity related proteins (PRPs), and this damage increased with aging.